2023
DOI: 10.1007/s11357-023-00970-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glycine administration on the characteristics of physiological systems in human adults: A systematic review

Janjira Soh,
Shivaanishaa Raventhiran,
Jasinda H. Lee
et al.

Abstract: Functional decline of physiological systems during ageing leads to age-related diseases. Dietary glycine increases healthy lifespan in model organisms and might decrease inflammation in humans, suggesting its geroprotective potential. This review summarises the evidence of glycine administration on the characteristics of eleven physiological systems in adult humans. Databases were searched using key search terms: ‘glycine’, ‘adult’, ‘supplementation’/ ‘administration’/ ‘ingestion’/ ‘treatment’. Glycine was adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 80 publications
0
1
0
Order By: Relevance
“…Besides its neuroactive role, glycine primarily influences anti-oxidative reactions and immune system [ 94 ]. In agreement with this knowledge, glycine has been used to prevent tissue injury, enhance anti-oxidative capacity, improve immunity, and treat metabolic disorders in obesity, diabetes and various inflammatory diseases [ 96 ]. Thus, consistently with the reported “geroprotective” effects of glycine, we cannot rule out that the negative correlation of this amino acid and the glycine/L-serine ratio with cognitive function in frail older individuals might represent an adaptive mechanism aimed at counteracting the systemic inflammation and metabolic dysfunctions that characterize frailty syndrome [ 12 , 25 ], rather than being causally linked to cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its neuroactive role, glycine primarily influences anti-oxidative reactions and immune system [ 94 ]. In agreement with this knowledge, glycine has been used to prevent tissue injury, enhance anti-oxidative capacity, improve immunity, and treat metabolic disorders in obesity, diabetes and various inflammatory diseases [ 96 ]. Thus, consistently with the reported “geroprotective” effects of glycine, we cannot rule out that the negative correlation of this amino acid and the glycine/L-serine ratio with cognitive function in frail older individuals might represent an adaptive mechanism aimed at counteracting the systemic inflammation and metabolic dysfunctions that characterize frailty syndrome [ 12 , 25 ], rather than being causally linked to cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The major rate-limiting factor in GSH synthesis in cells is the amount of cysteine present [40]. Glycine is also considered a rate-limiting factor in GSH production, and human studies have suggested that oral administration of glycine potentially counteracts oxidative stress and in ammation [41,42]. Therefore, dipeptides such as γ-Glu-Cys and Cys-Gly in cysteine peptides can be additional sources of cysteine as well as glutamyl acid and glycine to enhance intracellular GSH production when GSH is depleted due to UV-B-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…1 Representation of the multidisciplinary team and diagnostic and intervention approaches in academic healthy longevity clinics mance or alleviate dysfunction in early clinical studies in humans [8]. Among these compounds, nicotinamide mononucleotide (NMN) [9], alphaketoglutarate (AKG) [10], glycine [11], senolytics including fisetin and the combination of dasatinib plus quercetin (D + Q) [12], urolithin A [13], and spermidine [14] have garnered attention for their potential geroprotective effects. Additional clinical trials will be crucial in firmly establishing the potential role of supplements in delaying, preventing, alleviating, or treating diseases and disorders linked to fundamental aging mechanisms.…”
Section: ) Supplementsmentioning
confidence: 99%